Inside the teenage brain - Spinks, Sarah; Spin Free Productions; WGBH (Television station : Boston, Mass.); CTV Television Network; Discovery Channel Canada; PBS Video ([Alexandria, Va.] : PBS Video, 2002)
"It's the mystery of mysteries - especially to parents. Now the experts are exploring the recesses of the brain and finding explanations for why adolescents behave the way they do and how the new discoveries can change the way we teach, or perhaps even understand, our teenagers"--Container.
Originally broadcast as a segment of the television program: Frontline.
Senior producer, Sharon Tiller ; director of photography, Douglas Pike ; editor, Jeff Morgan ; executive producer, David Fanning.
DVD.
Closed-captioned.
Keywords: Cognition in adolescence; Pediatric neuropsychology; Teenagers; Brain -- Growth; Teenagers -- Family relationships; Teenagers -- Health and hygiene; Video recordings for hard of hearing people